What value do travelers put on connectivity to mobile phone and Internet networks in public transport? Empirical evidence from the Paris region. (December 2019) - Bounie, Nathan; Adoue, François; Koning, Martin; L'Hostis, Alain
Highlights: Travel time value in PT depend on connectivity to mobile phone and Internet. Stated preferences are used to study this phenomenon for the Paris region. Results are expressed in terms of "time multipliers". Time value reduced by 12% if PT users would enjoy an optimal connectivity. Abstract: Unlike the drivers of private vehicles, public transport (PT) users may perform secondary tasks during their primary travel activity. Moreover, Information and Communication Technologies may open up "multi-tasking" possibilities by allowing individuals to spend their travel time in more pleasant ways. This article proposes a tentative valuation of connectivity to mobile phone and Internet networks (MPIN) in PT, based on the stated preferences of 501 inhabitants of the Paris region. The surveyed individuals were presented with hypothetical trade-offs between travel time reductions and improvements in MPIN connectivity in PT. Econometric tests show that the values ascribed to better connectivity are higher when PT users perform various tasks with smartphones or tablets during their trips and when they experience a large number of connectivity problems in the reference situation. While heterogeneity between individuals has a minor direct impact, we propose a typology of PT users that captures variations in valuations. On average, the subjective value of travel time would be reduced by 12% if PT users benefited from optimal MPIN connectivity whilst traveling. Alternative "time multipliers" – for types of PT user, gradual connectivity improvements, different device-based tasks – are also proposed. Lastly, we apply our results to a cost-benefit analysis of a current project in the Paris region PT.